Comparison of IV Sucrose and IV Carboxymaltose in Patients with Anemia in Pregnancy - Basharat, Sundus; Zubair, Maryam; Adnan, Zubina (Indus Journal of Bioscience Research, 2025)
Background: Pregnancy-associated iron deficiency anemia is a major health problem for its role in causing maternal morbidity and undesirable perinatal outcomes. Standard therapy with intravenous iron sucrose consists of multiple frequent small infusions, with ferric carboxymaltose accepting larger single doses at shorter intervals. There remains sparse direct evidence for a comparison between their effectiveness in pregnancy. Objective: To compare the effectiveness of intravenous ferric carboxymaltose and intravenous iron sucrose in pregnant women with moderate to severe iron deficiency anemia. Study Design: Randomized controlled trial. Place and Duration of Study: This trial was conducted from June 2024 to November 2024 in the Department of Obstetrics and Gynecology, SKBZ Combined Military Hospital, Muzaffarabad. Methodology: Sixty pregnant women between 16 and 24 weeks of gestation, with hemoglobin levels ranging from 7 to 10 grams per deciliter, were randomized into two equal groups. One group received ferric carboxymaltose in single doses up to 1000 milligrams, while the other group received iron sucrose in divided doses not exceeding 600 milligrams per week. Hemoglobin and red cell indices were recorded at baseline and during follow-up at 3, 6, and 12 weeks. Results: Baseline demographic and clinical features were comparable between the two groups. After 12 weeks, mean hemoglobin significantly increased in the ferric carboxymaltose group (113.45±4.95 g/L) compared to the iron sucrose group (106.29±4.87 g/L). The average rise from baseline was greater with ferric carboxymaltose (29.32±3.23 g/L) than with iron sucrose (22.25±1.75 g/L, p